Using Artificial Intelligence Assisted Learning Technology on Augmented Reality-Based Manufacture Workflow - Li, Mingchao; Chen, Yuqiang (Frontiers in Psychology, 2022)
The manufacturing process is defined by the synchronous matching and mutual support of the event logic and the task context so that the work task can be perfectly completed by executing each step of the manufacturing process. However, in the manufacturing process of the traditional production environment, the on-site personnel are often faced with the situation that the on-site advice is required due to lack of experience or knowledge. Therefore, the function of the manufacturing process should be more closely connected with the workers and tasks. In order to improve manufacturing efficiency and reduce the error rate, this research proposed a set of manufacturing work knowledge frameworks to integrate the intelligent assisted learning system into the manufacturing process. Through Augmented Reality (AR) technology, object recognition technology is used to identify the components within the line of sight, and the assembly steps are presented visually. During the manufacturing process, the system can still feedback to the user in animation. To achieve the function equivalent to the on-the-spot guidance and assistance to solve the problem by a special person. Research experiments show that the operation of this intelligent assisted learning interface can more quickly recognize the manufacturing process work and solve problems, which greatly solves the situation of personnel with insufficient experience and knowledge.